1986
DOI: 10.1111/j.1476-5381.1986.tb11187.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the vascular endothelium on agonist‐induced contractions and relaxations in rat aorta

Abstract: 1 The influence of the vascular endothelium on agonist-induced contractions and relaxations has been measured using intact segments of rat aorta. Contiguous rubbed segments were used as controls. 2 Angiotensin II, histamine, noradrenaline, U46619 and UK14304 contracted both rubbed and intact tissues. The threshold spasmogenic concentrations of these agonists were lower in rubbed tissues than in intact preparations. 3 The sensitivity and responsiveness of tissues to angiotensin II, histamine, noradrenaline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
2
5

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 32 publications
(43 reference statements)
9
58
2
5
Order By: Relevance
“…Moreover, they demonstrate that the maximal response and the sensitivity of the tissue to All, whether given exogenously or locally formed from AI and TDP renin substrate, were increased by removal of the endothelium. Our observations concerning the influence of the endothelium on the response to exogenous All confirm previous studies performed in the rat aorta and in some other vascular tissues, such as bovine coronary artery, rabbit mesenteric and coeliac arteries (Oshiro et al, 1985;Bullock et al, 1986;Gruetter et al, 1988). However, in other vessels such as rabbit aorta or canine carotid artery, the endothelium has no effect on the contractile response to All (Saye et al, 1984;D'Orleans-Juste et al, 1985).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, they demonstrate that the maximal response and the sensitivity of the tissue to All, whether given exogenously or locally formed from AI and TDP renin substrate, were increased by removal of the endothelium. Our observations concerning the influence of the endothelium on the response to exogenous All confirm previous studies performed in the rat aorta and in some other vascular tissues, such as bovine coronary artery, rabbit mesenteric and coeliac arteries (Oshiro et al, 1985;Bullock et al, 1986;Gruetter et al, 1988). However, in other vessels such as rabbit aorta or canine carotid artery, the endothelium has no effect on the contractile response to All (Saye et al, 1984;D'Orleans-Juste et al, 1985).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, methylene blue, an inhibitor of EDRF, produced the same potentiation of the contractile response to All as endothelium removal. This indicates that, in the rat aorta, the inhibitory effect of the endothelium on the contraction induced by All may be attributed to the release of EDRF, as has been proposed by Bullock et al (1986) andGruetter et al (1988).…”
Section: Discussionmentioning
confidence: 53%
“…Higher levels of cyclic GMP in unrubbed vessels as compared to those in matched rubbed vessels have been ascribed to the effect of this basal EDRF (Holzmann, 1982;Rapoport & Murad, 1983;Diamond & Chu, 1983;Bigaud et al, 1984;Martin et al, 1986;Spedding et al, 1986;Bullock et al, 1986;Gruetter & Lemke, 1986b). As a consequence, basal levels of cyclic GMP are regarded as an index of the release of basal EDRF.…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenaline-induced precontractions were 1.98 + 0.60g (0), 1.72 ± 0.44g (0) animal arteries (Cocks & Angus, 1983;Miller & Vanhoutte, 1985;Angus et al, 1986ab;Bullock et al, 1986 and UK 14,304 (0.1 pM-IO pM) were devoid of any relaxing activity (n = 3 and 2, respectively), although the preparations could be relaxed by acetylcholine.…”
Section: Contractile Experimentsmentioning
confidence: 99%
“…Although xylazine and clonidine did not produce vascular responses in non-pretreated preparations, it is not clear that alpha-2 agonists have vasodilatory effects in preconstricted preparations. It is necessary to examine effects of alpha-2 agonists on preconstricted vascular preparations and/or endothelium rubbed vascular preparations in future, becauses it has been reported that alpha-2 agonists cause vascular relaxations via alpha-2 receptors (Cocks and Angus 1983 ; Angus et al 1986 ;Bullock et al 1986). …”
Section: Discussionmentioning
confidence: 99%